Предмет: Математика,
автор: Аноним
Помогите решить плиз !!
3х+6(1-х)=-2(2+х)
1,7-8(х-1)=3,7+2х
6(х-1)+12(3-2х)=45-17х
12(1-х)-4=2(4х+6)
0,5(2х-1)-х=6,5
Ответы
Автор ответа:
0
3х+6(1-х)=-2(2+х)
3x+6-6x=-4-2x
x=10
1,7-8(х-1)=3,7+2х
1,7-8x+8=3,7+2x
10x=6
x=0,6
6(х-1)+12(3-2х)=45-17х
6x-6+36-24x=45-17x
x=-15
12(1-х)-4=2(4х+6)
12-12x-4=8x+12
20x=-4
x=-0,2
3x+6-6x=-4-2x
x=10
1,7-8(х-1)=3,7+2х
1,7-8x+8=3,7+2x
10x=6
x=0,6
6(х-1)+12(3-2х)=45-17х
6x-6+36-24x=45-17x
x=-15
12(1-х)-4=2(4х+6)
12-12x-4=8x+12
20x=-4
x=-0,2
Автор ответа:
0
0,5(2х-1)-х=6,5
Автор ответа:
0
x-0,5-x=6,5
Автор ответа:
0
нет решения
Автор ответа:
0
-0,5 не равно 6,5
Автор ответа:
0
спс
Похожие вопросы
Предмет: Алгебра,
автор: ajlaordokova
Предмет: Математика,
автор: ferewer3466
Предмет: Химия,
автор: ulianakirpota
Предмет: Математика,
автор: боня14
Предмет: География,
автор: Vitalaan